Application of Response Surface Methodology to Optimize Ammonia Volatilization Determination by Enclosure Method. Issue 15 (21st August 2020) - Shakeel, Sarah; Mahmood, Rashid; Fatima, Ammara; Ali, Sajid
ABSTRACT: In the enclosure method, ammonia volatilization from an enclosed soil is commonly estimated by hanging acid-soaked polyfoam pads over the soil sample in an enclosed bottle. Response surface methodology (RSM) was used to optimize polyfoam density (D), pad height (H) and pad saturation with an acid solution (S) to maximize ammonia collection in the polyfoam pads. Three central composite design (CCD) experiments with three polyfoams having low (0.013 g cm −3 ), medium (0.026 g cm −3 ), and high (0.037 g cm −3 ) D were conducted. The pads utilized had heights of 1.25, 2.50, and 3.75 cm saturated with an acid solution (9.8% H3 PO3 plus 2% glycerol) to a weight of 5, 9, and 13 times that of the dry pad weight. Models developed for medium and high-density polyfoams were sufficiently reliable to predict ammonia collection response in terms of H and S. The response increased linearly with H and quadratically with S. High D pads collected about 13% more ammonia than that of low or medium D pads. The models predicted maximum ammonia collection in polyfoam pads of density 0.037 g cm −3, height 3.75 cm, and at acid saturation of 10.58 times of the dry pad weight.